2009
DOI: 10.1111/j.1743-6109.2009.01375.x
|View full text |Cite
|
Sign up to set email alerts
|

The ENDOTRIAL Study: A Spontaneous, Open-Label, Randomized, Multicenter, Crossover Study on the Efficacy of Sildenafil, Tadalafil, and Vardenafil in the Treatment of Erectile Dysfunction

Abstract: Introduction The three effective, commercially available drugs for the treatment of erectile dysfunction—sildenafil, vardenafil, and tadalafil—inhibit the same substrate, the erectolytic enzyme phosphodiesterase type 5 (PDE5). Although there are pharmacological differences between these three compounds, few comparative studies have been conducted to date. Aim The aim of this study was to determine the efficacy of sildenafil, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 52 publications
1
45
0
1
Order By: Relevance
“…The efficacy and safety of vardenafil have been tested in several randomized trials, including men with various underlying conditions [25, 5963]. All these studies documented efficacy that was retained irrespective of the medication used to treat the underlying disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy and safety of vardenafil have been tested in several randomized trials, including men with various underlying conditions [25, 5963]. All these studies documented efficacy that was retained irrespective of the medication used to treat the underlying disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Sponsored clinical trials for drug registration purposes are often biased by the tendency to recruit populations with lower CVRs than seen in end users in a real-life setting [25]. Therefore, the safety and efficacy of PDE5i in high CV risk populations require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…2 Patients using different PDE5 inhibitors have a similar perception of improvement after treatment. 245 Direct comparative studies are lacking and preference studies are inconclusive and biased. 246 In any case, patients should be given the opportunity to try different PDE5 inhibitors.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…A recent prospective, randomized, multicentre crossover study demonstrated an overall equivalence in the subjective perception of treatment benefits between all PDE5I, although patients and their partners may have individual preferences. 47 Adverse events from PDE5I include headache, facial flushing, nasal congestion, myalgia, back pain and blurred or disturbed vision; these effects are generally attributed to cross-reactivity with other PDE isoforms. The nature and frequency of adverse events are similar in patients older than 65 years compared with their younger counterparts.…”
Section: Treatmentmentioning
confidence: 99%